Increasing The Capacity of Local Communities through Institutional Reorganization of Dekso Tourism Village in Banjararum Village, Kulon Progo Regency - Devi, Laksmi Yustika; Wirakusuma, Gilang; Jatmiko, Bambang Agung; Kusuma, Puspita; Irdana, Nuryuda; Khoir, Riziq Apani; Nasion, Marsa Kamila; Kusuma, Luqman Wiranata (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2025)
Dekso Tourism Village in Kulon Progo Regency, during its five-year period after establishment, faces difficulties to maintain and develop its tourism busines. Internal problems of the management become an obstacle to the development of the village so that it can compete with other tourism villages and has an economic impact on the community. The tourism village development program is one form of community-based development implementation. The active role of the community itself is very important in the management process. Therefore, this community service program was carried out to help solving the village’s problems through three stages of implementation methods, namely the process of awareness, capacitating, and enrichment. Improved governance was carried out by reorganizing the new management based on established criteria and referring to the collegial collective principle. Reorganization also includes strengthening institutional cooperation with BUMDes as the parent company, POKDARWIS and other organizations involved in the tourism village. In addition, in order to strengthen the tourism village governance, the formation of a village regulation (PerKal) on tourism villages is also part of this service program. This legal umbrella will encourage cooperation between related parties to be more systematic, protect tourism village activities, as well as be the guidelines for future tourism development in Banjararum.